2015
DOI: 10.1002/app.43295
|View full text |Cite
|
Sign up to set email alerts
|

Modification of wood flour/PLA composites by reactive extrusion with maleic anhydride

Abstract: MA modified wood flour/PLA composites were prepared by one-step reactive extrusion, in which wood flour and poly(lactic acid) (PLA) were used as raw material, maleic anhydride (MA) was used as modifier, and dicumyl peroxide (DCP) was used as initiator. The influences of MA concentration on the morphology, thermal stability, rheological, and mechanical properties of the composites were studied. The addition of MA improved the compatibility of the composites significantly. The thermal and rheological results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 28 publications
1
42
0
1
Order By: Relevance
“…This is an indication that enhancing the interaction between coir fibers and PLA led to a crosslinked network structure in the biocomposites in which PLA chains mobility was reduced; i.e. if the interaction between coir fibers and PLA is strong enough, this reduces the polymer chains mobility which is related to the glass transition . In the same way, it is possible that the fiber‐matrix interaction in CT‐PMVE‐BC decreases the chain mobility leading to lower T g by 7°C.…”
Section: Resultsmentioning
confidence: 95%
“…This is an indication that enhancing the interaction between coir fibers and PLA led to a crosslinked network structure in the biocomposites in which PLA chains mobility was reduced; i.e. if the interaction between coir fibers and PLA is strong enough, this reduces the polymer chains mobility which is related to the glass transition . In the same way, it is possible that the fiber‐matrix interaction in CT‐PMVE‐BC decreases the chain mobility leading to lower T g by 7°C.…”
Section: Resultsmentioning
confidence: 95%
“…These compatibilized composites yielded superior mechanical performances than corresponding uncompatibilized composites. Maleic anhydride grafted polymers have been used as a compatibilizer to improve the compatibility between the lignocellulosic fibers and the PHBV matrix . Organic free radical initiators are also used to enhance the compatibility between the polymer matrix and the natural fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Csikos et al extended the study to the effect of the MA-PLA content [Csikós et al, 2015], with increased amounts of MA-PLA enhancing the interfacial adhesion parameter, and thus the tensile strength of PLA/WF composites, with a more pronounced effect with increasing number of functionality and compatibiliser amount. However, contradictory results were reported by Lv et al who found that the compatibiliser amount exhibited an insignificant effect on mechanical properties of PLA/30 wt% WF composites produced using a single-step reactive extrusion [Lv et al, 2016].…”
Section: Maleic Anhydride Grafting On Matrixmentioning
confidence: 88%
“…Given the attractive properties of PLA, extensive research has been undertaken on optimising the uncompatbilised composites with WF [Csizmadia et al, 2013;Febrianto et al, 2006;Finkenstadt & Tisserat, 2010;Gregorova et al, 2011;Guo et al, 2012a;Huda et al, 2005;Lee et al, 2008;Liu et al, 2013;Liu et al, 2015;Liu et al, 2016;Lv et al, 2016;Lv et al, 2015;Peltola et al, 2014;Petinakis et al, 2009;Pilla et al, 2008;Pilla et al, 2009;Qiang et al, 2012;Shah, B. L. et al, 2008] The addition of wood reinforcement had a mixed effect on mechanical strength but the type and origin of wood reinforcement has a significant influence on composites' properties. Peltola et al compared the properties of PLA-based and PP-based composites reinforced by four different types of woodbased reinforcements (bleach kraft pulp from pine, eucalyptus and birch, thermomechanical spruce pulp and pine flour) [Peltola et al, 2014].…”
Section: Properties Of Pla-based Wpcsmentioning
confidence: 99%
See 1 more Smart Citation